Risk and Protective Factors in the COVID-19 Pandemic: A Rapid Evidence Map - Elmore, Rebecca; Schmidt, Lena; Lam, Juleen; Howard, Brian E.; Tandon, Arpit; Norman, Christopher; Phillips, Jason; Shah, Mihir; Patel, Shyam; Albert, Tyler; Taxman, Debra J.; Shah, Ruchir R. (Frontiers in Public Health, 2020)
Background: Given the worldwide spread of the 2019 Novel Coronavirus (COVID-19), there is an urgent need to identify susceptibility factors and expose areas of insufficient understanding. Emerging tools, such as the Rapid Evidence Map (rEM), are being developed to systematically characterize the literature. We sought to generate a rEM of risk and protective factors to comprehensively inform areas that impact COVID-19 outcomes for different sub-populations in order to better protect the public. Methods: We developed a protocol that includes a study goal, study questions, a PECO statement, and a process for screening literature by combining semi-automated machine learning with the expertise of our review team. We applied this protocol to reports within the COVID-19 Open Research Dataset (CORD-19) that were published in early 2020. SWIFT-Active Screener was used to prioritize records according to pre-defined inclusion criteria. Relevant studies were categorized by risk/ protective status; susceptibility category (Behavioral, Physiological, Demographic and Environmental); and affected sub-populations. Using tagged studies, we created a rEM for COVID-19 susceptibility that reveals: (1) current lines of evidence; (2) knowledge gaps; (3) areas that may benefit from systematic review. Results: We imported 4,330 titles and abstracts from CORD-19. After screening 3,521 to achieve 99% estimated recall, 217 relevant studies were identified. Most included studies concerned the impact of underlying comorbidities (Physiological); age and gender (Demographic); and social factors (Environmental) on COVID-19 outcomes. Though the findings were manifold, older males with comorbidities were commonly reported to have the poorest outcomes. We noted a paucity of COVID-19 studies among children and susceptible sub-groups, including pregnant women, racial minorities, refugees/migrants, and healthcare workers, with few studies examining protective factors. Conclusion: Using rEM analysis, we synthesized the recent body of evidence related to COVID-19 risk and protective factors. The results provide a comprehensive tool for rapidly elucidating COVID-19 susceptibility patterns and identifying resource-rich/resource-poor areas that may benefit from future investigation as the pandemic evolves.